2011
DOI: 10.1007/s00122-011-1631-7
|View full text |Cite
|
Sign up to set email alerts
|

Association mapping in an elite maize breeding population

Abstract: Association mapping (AM) is a powerful approach to dissect the genetic architecture of quantitative traits. The main goal of our study was to empirically compare several statistical methods of AM using data of an elite maize breeding program with respect to QTL detection power and possibility to correct for population stratification. These models were based on the inclusion of cofactors (Model A), cofactors and population effect (Model B), and SNP effects nested within populations (Model C). A total of 930 tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 40 publications
3
55
1
Order By: Relevance
“…Model-A generally detected more QTL than Model-B, which are likely QTL due to exploitation of variance among populations (Figure 3; Liu et al, 2011). This corroborates findings of simulation studies (Yu et al, 2008) reporting that QTL detection power was higher for a model including only cofactors (Model-A) compared with a model, which in addition included a population effect (Model-B).…”
Section: Properties Of the Jlam Populationsupporting
confidence: 84%
See 4 more Smart Citations
“…Model-A generally detected more QTL than Model-B, which are likely QTL due to exploitation of variance among populations (Figure 3; Liu et al, 2011). This corroborates findings of simulation studies (Yu et al, 2008) reporting that QTL detection power was higher for a model including only cofactors (Model-A) compared with a model, which in addition included a population effect (Model-B).…”
Section: Properties Of the Jlam Populationsupporting
confidence: 84%
“…The difference between Model-A and Model-B with regard to the explained genotypic variance was much more pronounced for beet yield, sugar content and potassium content than for the other three traits (Table 2). A recent publication indicated that this might be due to higher associations between the phenotype and the population structure for some traits, or by higher R 2 values of the population effect (Liu et al, 2011). None of these parameters, however, explained the differences in this data set (Supplementary Table 3).…”
Section: Properties Of the Jlam Populationmentioning
confidence: 76%
See 3 more Smart Citations